PWE-077 Outcome following resection of biliary cystadenoma – a single centre experience. (22nd June 2015) - Pitchaimuthu, M; Aidoo-Micah, G; Coldham, C; Sutcliffe, R; Roberts, K; Muiesan, P; Isaac, J; Mirza, D; Marudanayagam, R
Abstract : Introduction: Biliary cystadenoma (BCA) are rare, benign, potentially malignant cystic lesions of the liver, accounting for less than 5% of cystic liver tumours. These lesions have potential for recurrence and malignant transformation. The aim of the study was to analyse the outcome following resection of biliary cystadenoma from a single tertiary centre. Method: Patients who had resection of BCA between 1993 and 2014 (21 years) were included in the study. The data were obtained form a prospectively maintained liver surgical and pathological database. Patient demographics, clinico-pathological characteristics, operative data and post-operative outcome were collected. Results: 29 patients had surgery for BCA. Median age was 62 (IQ 48–74) years and the Male:Female ratio was 28:1. The main clinical presentation was abdominal pain (74%) followed by jaundice (20%), abdominal mass (14%) and deranged LFTs (3%). On pre-operative imaging, single cyst was seen in 76% of patients. The majority of cysts were found at central location (48%). Cyst characteristics included septations (48%), wall thickening (31%), wall irregularity (38%), papillary projections (10%) and mural nodule (3%). Surgical procedures performed as follows: atypical liver resection (45%), left hemihepatectomy (34%), right hemihepatectomy (10%), excision of extra hepatic bile duct (7%) and left lateral segmentectomy (3%). Three patients had de-roofing for suspected simple liver cyst, which were confirmed on histology as biliary cystadenoma. All had re-resection with clear margins. Median length of stay was 7 (IQ 6.5 – 8.5) days. 2 patients developed bile leak, one each managed conservatively and with ERCP. There was no peri-operative mortality. None of the patients had evidence of malignancy on final histology. Median follow-up was 11 (IQ 2–44) months. One patient developed delayed biliary stricture requiring reconstruction. One died 11 years later due to development of inoperable cholangiocarcinoma. Disclosure of interest: None Declared. Conclusion: Biliary cystadenomas can be resected safely with significantly low morbidity. Malignant transformation and recurrence are rare. Complete surgical resection provides a cure.